The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1108/mmms-02-2022-0015
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation of a viscoelastic pipeline vibration under pulsating fluid flow

Abstract: PurposeThe purpose of this study is to create a mathematical model, a numerical algorithm and a computer program for studying the vibration of composite pipelines based on the theory of beams used in the oil and gas industry, agriculture and water management, housing and communal services and other areas.Design/methodology/approachA mathematical model of vibration of a viscoelastic pipeline based on the theory of beams with a pulsating fluid flowing through it was developed. Using the Bubnov-Galerkin method, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…The study of equation (16) shows that it is an integral Fredholm equation of the second kind with a weak singularity. Its unique solvability follows from the uniqueness of the solution to the problem.…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…The study of equation (16) shows that it is an integral Fredholm equation of the second kind with a weak singularity. Its unique solvability follows from the uniqueness of the solution to the problem.…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…In addition, the fluid–solid coupling method was used to investigate the vibrations of fluid-conveying pipelines (Matta and Szasz, 2018; Chen et al , 2021b; Lin and Wang, 2019). Khudayarov and Turaev (2022) established a mathematical model of composite pipe vibration and investigated the vibration problem of a composite pipe under the action of a pulsating fluid through the established model. The results indicated that increases in material viscosity decrease the critical flow velocity that can cause pipeline vibration.…”
Section: Introductionmentioning
confidence: 99%
“…The causes of vibration in the piping of the main line pumps and the influence of frequency regulation on the level of vibration of the main line pump are analyzed. B Khudayarov [8] developed a computational algorithm for solving problems of vibrations in composite pipelines conveying pulsating liquid. The stability and amplitude-time characteristics of vibration in composite pipelines with pulsating fluid flowing in them are studied for a wide range of changes in the parameters of deformable systems and fluid flow.…”
Section: Introductionmentioning
confidence: 99%